2017
DOI: 10.3766/jaaa.15125
|View full text |Cite
|
Sign up to set email alerts
|

Speech Recognition in Nonnative versus Native English-Speaking College Students in a Virtual Classroom

Abstract: Acoustics in the classroom are an important consideration for nonnative speakers who are proficient in English and enrolled in college. To address the need for a clearer speech signal by nonnative students (and for all students), universities should follow ANSI recommendations, as well as minimize background noise in occupied classrooms. Behavioral/instructional strategies should be considered to address factors that cannot be compensated for through acoustic design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Results also indicate that bilingual students in university settings may struggle to understand masked speech even if they are highly proficient in the target language but have learned English later in life. This result is consistent with that of Neave-DiToro et al (2017). That study evaluated masked speech recognition multitalker babble, with and without reverberation, in university students who were either native English speakers or late learners of English.…”
Section: Practical Implicationssupporting
confidence: 88%
See 2 more Smart Citations
“…Results also indicate that bilingual students in university settings may struggle to understand masked speech even if they are highly proficient in the target language but have learned English later in life. This result is consistent with that of Neave-DiToro et al (2017). That study evaluated masked speech recognition multitalker babble, with and without reverberation, in university students who were either native English speakers or late learners of English.…”
Section: Practical Implicationssupporting
confidence: 88%
“…Although it is not clear why some studies have found differences between monolingual and early bilingual participants (Krizman et al, 2017;Neave-DiToro et al, 2017) and others have not (Calandruccio & Zhou, 2014;Reetzke et al, 2016;Shi, 2009), there are some listener variables that could explain this discrepancy. These factors include, but are not limited to, listener age, access to education, and daily language use.…”
Section: Listener Variables Other Than Age Of Acquisitionmentioning
confidence: 95%
See 1 more Smart Citation
“…By now, it is reasonably well established that bilingualism slows down or otherwise impairs lexical access: Bilinguals, compared to monolinguals, are typically slower at picture naming (Gollan et al, 2005b), or name fewer pictures from standardized sets (e.g., Boston Naming Test; Roberts et al, 2002; Gollan et al, 2005b, 2007; Bialystok et al, 2008b; Tao et al, 2015). Moreover, bilinguals correctly identify fewer words in noise (Rogers et al, 2006) and exhibit greater so-called tip-of-the-tongue (TOT) retrieval states that occur when individuals have the phenomenological experience of being on the verge of, but temporarily unable, to access information in long-term memory (Gollan and Silverberg, 2001; Gollan and Acenas, 2004; Gollan et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…Children with special needs may require even more favorable SNR and shorter reverberation times (American Speech-Language-Hearing Association, 2005). The group with special needs with regard to the needed SNR also include children with another first language (Tabri et al, 2011) since many studies have shown that non−native adult speakers have more difficulty perceiving speech in noise than native speakers (e.g., McAllister, 1990; Crandell and Smaldino, 1996; Rogers et al, 2006; Tabri et al, 2011). In a study including Swedish children learning English, Hurtig et al (2016) reported fewer recalled words when presented in L2 compared to words presented in L1.…”
Section: Introductionmentioning
confidence: 99%